Primary radiotherapy in progressive optic nerve sheath meningiomas: a long-term follow-up study. Issue 5 (6th May 2010) - Saeed, Peerooz; Blank, Leo; Selva, Dinesh; Wolbers, John G; Nowak, Peter J C M; Geskus, Ronald B; Weis, Ezekiel; Mourits, Maarten P; Rootman, Jack
Abstract : Background/aims: To report the outcome of primary radiotherapy in patients with progressive optic nerve sheath meningioma (ONSM). Methods: The clinical records of all patients were reviewed in a retrospective, observational, multicentre study. Results: Thirty-four consecutive patients were included. Twenty-six women and eight men received conventional or stereotactic fractionated radiotherapy, and were followed for a median 58 (range 51–156) months. Fourteen eyes (41%) showed improved visual acuity of at least two lines on the Snellen chart. In 17 (50%) eyes, the vision stabilised, while deterioration was noted in three eyes (9%). The visual outcome was not associated with age at the time of radiotherapy (p=0.83), sex (p=0.43), visual acuity at the time of presentation (p=0.22) or type of radiotherapy (p=0.35). Optic disc swelling was associated with improved visual acuity (p<0.01) and 4/11 patients with optic atrophy also showed improvement. Long-term complications were dry eyes in five patients, cataracts in three, and mild radiation retinopathy in four. Conclusion: Primary radiotherapy for patients with ONSM is associated with long-term improvement of visual acuity and few adverse effects.